CAT and MRI Studies of Spinal Cord Injured Rats Implanted with PPy/I - Morales-Guadarrama., A.; Salgado-Ceballos., H.; Morales., J.; Ríos, C.; Cruz., G. J.; Díaz-Ruiz., A.; Olayo., M. G.; Álvarez-Mejía., L.; Mondragón-Lozano., R.; Olayo., R. (Revista Mexicana de Ingenieria Biomedica, 2013)
Polymers synthesized by plasma derived from pyrrole have been recently implanted in rats with spinal cord injuries (SCI) using a complete section model; the polymers contribute to the functional recovery after the injury. In this work, the SCI in rats was studied using noninvasive techniques such as magnetic resonance imaging (MRI). Also, computerized axial tomography was taken chronologically with and without polymeric implants. 3D reconstructions were used to follow the structural arrangement, the location of the implant and the formation of cysts. MRI shows a clear differentiation between white and gray matter, the implanted material and cysts due to secondary damage after the injury.